Life expectancy and parental education in Germany - Mathias Huebener (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This study analyses the relationship between life expectancy and parental education. Based on data from the German Socio-Economic Panel Study and survival analysis models, we show that maternal education is related to children's life expectancy - even after controlling for children's own level of education. This applies equally to daughters and sons as well as to children's further life expectancies examined at age 35 to age 65. This pattern is more pronounced for younger cohorts. In most cases, the education of the father is not significantly related to children's life expectancy. Neither the vocational training nor the occupational position of the parents in childhood, which both correlate with household income, can explain the connection. The health behaviour of the children and the health accumulated over the life course appear as important channels. This study extends the previous literature that focused mostly on the relationship between individuals' own education and their life expectancy. It implies that the link between education and life expectancy is substantially stronger and that returns to education are higher if the intergenerational component is considered.
Keywords: I12; I14; I26; 330; health inequality; returns to education; mortality; parental background; human capital; survival analysis